KEKALAHAN CALON INDEPENDEN DALAM PEMILHAN BUPATI DAN WAKIL BUPATI KABUPATEN KARIMUN TAHUN 2015 - Syahri Ramadhani Sinuraya; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Participation of Independent candidates in general election of regional head based on many disappointments felt both from among themselves and society at large who feel harmed by the mechanism of election conducted by political parties. Karimun district is one of district that follow general election of regional head simultaneously on December 9th, 2015 present the candidates who used individual and independent path. In general election of regional head result of karimun district, the independent candidats suffered defeat, but there is interesting thing to be examined, difference of vote acquisition that earned by independent candidates is different with support terms that submitted by independent candidates. The aim of this research was to determined the difference because between vote acqusition that earn by independent candidates and support terms that submitted by independent candidates.This research using quantitative research aproach with kind of descriptive research. Data collection techniques used are documentation, and interview. Data analysis used limited to data peocessing techniques or facts gained by developing relevant categories with the aim of research and interpretations that are guided by appropriate theoryThe result of this research show the difference of vote acquisition and support terms caused by the existence of legal support terms caused by the existence of legal suppor uncertainty, support in the form of ID Cards only as a condition only so than can maniputate. This is avidenced by the fact that there are still people who withdraw their support by filling out the revocation form that provided by the KPU when recapitulation support.Keywords: Independent Candidates, General Election of Regional Head